FENOMENA DIGITAL HOARDING DI KALANGAN MAHASISWA POLITEKNIK MUHAMMAD DAHLAN: ANALISIS HUBUNGAN ANTARA KECEMASAN INFORMASI DENGAN KEENGGANAN MENGHAPUS DATA DIGITAL - Kiki Rizki Aulia; Nur Eka Dzulfaijah; Muhd Firmansyah (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2026)
This study was motivated by the growing phenomenon of digital hoarding among female students, characterized by the excessive accumulation and retention of digital data accompanied by a persistent reluctance to delete it. This phenomenon is believed to be closely linked to a psychological condition known as information anxiety, defined as an individual's apprehension about losing information that may prove valuable in the future. Accordingly, this study aimed to: (1) identify the level of information anxiety among female students at Muhammad Dahlan Polytechnic; (2) analyze the level of reluctance to delete digital data as an indicator of digital hoarding behavior; and (3) examine the relationship between information anxiety and reluctance to delete digital data. This study adopted a quantitative approach with a correlational research design. The sample comprised 50 active female students selected through purposive sampling. Data were collected using two Likert-scale questionnaires that had undergone validity and reliability testing—one measuring information anxiety (15 items) and the other measuring digital hoarding behavior (15 items). Data were analyzed using descriptive statistics and Pearson correlation analysis. The findings indicated that the majority of respondents exhibited high levels of both information anxiety (70.0%) and digital hoarding behavior (72.0%). Pearson correlation analysis yielded a coefficient of r = 0.689 (p < 0.001), indicating a strong, statistically significant positive relationship between information anxiety and reluctance to delete digital data. These findings underscore the need for digital literacy interventions and gender-sensitive mental health support within higher education institutions to mitigate the adverse impact of digital hoarding on female students' academic productivity.